La internacionalización de la educación superior como elemento intrínseco en los procesos de generación del conocimiento científico, y del desarrollo tecnológico que apuntan a la innovación. (2011)
The internationalization of higher education that has emerged with unusual force from the globalization process is recovering its original character and has returned to the essential functions of educational institutions. International and intercultural areas impose unprecedented challenges to the structure and management of education, particularly in the fields of research, teaching, autonomy and community service. It also becomes a dynamic that necessarily impacts on the level of educational quality. Internationalization is presented within the framework of a new university that requires sustainable human development, supports solidarity, the culture of peace, excellence and commitment to local, regional and international environments.